A study of alpha-set process and proposed sand reclamation system in Malaysia / Tengku Mohd Faris Tengku Othman and Ismayadi Mat Adam - Tengku Othman, Tengku Mohd Faris; Mat Adam, Ismayadi (1994)
This project is to study about the series of operations which the bonded sand is submitted after mold breakdown. The operation that we called it sand reclamation system is functioning to reconditions the sand for its possible use. Why need to reclaim? It is because of legislative regulation are increasingly restrictive a landfill disposal, sand is finite resources and reclaimed sand can be of a higher quality than new sand. After knowing in sand reclamation, we come out with the concept design including problem analysis, assessment of the problem, evaluating the alternatives and finally with the proposed method of sand reclamation in Malaysia. The proposed method is based on environmental consideration, effectiveness and economic view.